Over-the-Counter Monograph Safety, Innovation, and Reform Act. Issue 2 (2021) - Gardiner, Jason; Kesselheim, Aaron S.
Abstract: Over-the-counter (OTC) drugs are ubiquitous in the US. Policymakers have long debated how to modernize the system for making determinations of safety and effectiveness and addressing safety issues with OTC drugs.